Segmental and tandem chromosome duplications led to divergent evolution of the chalcone synthase gene family in Phalaenopsis orchids. (2nd August 2018) - Kuo, Yi-Tzu; Chao, Ya-Ting; Chen, Wan-Chieh; Shih, Ming-Che; Chang, Song-Bin
Abstract: Background and Aims: Orchidaceae is a large plant family, and its extraordinary adaptations may have guaranteed its evolutionary success. Flavonoids are a group of secondary metabolites that mediate plant acclimation to challenge environments. Chalcone synthase (CHS) catalyses the initial step in the flavonoid biosynthetic pathway. This is the first chromosome-level investigation of the CHS gene family in Phalaenopsis aphrodite and was conducted to elucidate if divergence of this gene family is associated with chromosome evolution. Methods: Complete CHS genes were identified from our whole-genome sequencing data sets and their gene expression profiles were obtained from our transcriptomic data sets. Fluorescence in situ hybridization (FISH) was conducted to position five CHS genes to high-resolution pachytene chromosomes. Key Results: The five Phalaenopsis CHS genes can be classified into three groups, PaCHS1, PaCHS2 and the tandemly arrayed three-gene cluster, which diverged earlier than those of the orchid genera and species. Additionally, pachytene chromosome-based FISH mapping showed that the three groups of CHS genes are localized on three distinct chromosomes. Moreover, an expression analysis of RNA sequencing revealed that the five CHS genes had highly differentiated expression patterns and its expression pattern-based clustering showed high correlations between sequence divergences and chromosomal localizations of the CHS gene family in P. aphrodite . Conclusions: Based on their phylogenetic relationships, expression clustering analysis and chromosomal distributions of the five paralogous PaCHS genes, we proposed that expansion of this gene family in P. aphrodite occurred through segmental duplications, followed by tandem duplications. These findings provide information for further studies of CHS functions and regulations, and shed light on the divergence of an important gene family in orchids.